Thai sentiment terms construction using the hourglass of emotions - Lertsuksakda, Rathawut; Netisopakul, Ponrudee; Pasupa, Kitsuchart (My University, 2014)
Most of the current sentiment analysis techniques classifies emotions into two classes which are positive and negative. Some works classify them as positive, negative and objective (neutral). In fact, there are many kinds of emotions in human mind. Recently, psychological viewpoints have influenced most of the works in sentiment analysis. This psychology perspective was adopted to classify human emotions into a wider range, and in a more accurate manner. This paper reviews the adopted computational representation of emotions the so-called Hourglass of Emotion. This paper also proposes a construction of Thai sentiment resource based on such representation for Thai sentiment term tagging. A preliminary sentiment text tagging result shows that the resource as an ontology can be successfully used to tag sentiment text in Thai children stories. © 2013 IEEE.
Keywords: Bidirectional translation; Sentic computing; Sentiment analysis